Experimental and Numerical Study on Influence of Wheel Attachments on Resistance Performance of Amphibious Vessel for Marine Debris Collection - Won-June Jeong; Seol Nam; Jong-Chun Park; Hyeon Kyu Yoon (Journal of Marine Science and Engineering, 2024)
This study aims to investigate the influence of wheel configurations on hydrodynamic resistance of an amphibious vessel through experiments and simulations. To evaluate the resistance performance associated with wheel attachments, three configurations were examined: vessel without attachments, with caterpillars, and with both caterpillars and shoe−paddles. A comprehensive series of computational fluid dynamics (CFD) simulations were conducted for these attachment types, complemented by experimental validations. The Volume-of-Fluid (VOF) model was employed in CFD simulations to capture the free surface movement, and the Dynamic Fluid–Body Interaction (DFBI) model was adopted to represent the two-degree-of-freedom motion of the vessel, specifically trim and sinkage. The total resistance derived from CFD simulations was calculated across a range of Froude numbers (Fns), including the design speed of the target vessel, and validated through model tests conducted in a wave basin equipped with a towing facility. The analysis indicated a general increase in resistance when attachments were added to the amphibious vessel. Remarkably, at the design speed (Fn = 0.27), the total resistance with both caterpillars and shoe−paddles exceeded that of the configuration without any attachments by more than 75.7%. These results provide crucial insights for the preliminary design stage of amphibious vessels, particularly those intended for marine debris collection in hard-to-reach areas.